Degradable vinyl copolymers through thiocarbonyl addition–ring-opening (TARO) polymerization. Issue 1 (28th November 2018) - Bingham, Nathaniel M.; Roth, Peter J.
Abstract : Radical ring-opening polymerization of a thionolactone gives degradable thioester-functional polymers. Abstract : The radical copolymerization of the thionolactone dibenzo[ c, e ]oxepane-5-thione with acrylates, acrylonitrile, and N, N -dimethylacrylamide afforded copolymers containing a controllable amount of backbone thioesters which could be selectively cleaved. The process is compatible with RAFT polymerization and promising for the development of advanced degradable polymers.